2014
DOI: 10.1186/s13065-014-0071-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of phospholipid LB film studied layer by layer with AFM

Abstract: BackgroundPhospholipid, a main component of cell membrane, has been explored as a model system of the cell membrane and temporary scaffold materials in recent studies. The mechanical properties of phospholipid layers are essentially interesting since it is involved in several biological processes.ResultsHere, the nanomechanical properties such as indentation force, adhesion force and DMT (Derjaguin-Müller-Toporov) modulus of 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) Langmuir-Blodgett (LB) films were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
2
0
1
Order By: Relevance
“…The adhesive response for erucamide monolayer was likely affected by the underlying silica surface, thus slightly higher than that obtained for the bilayers or multilayers, for which the adhesive properties became dominated by the erucamide layers. This is consistent with report by Balzer et al in their AFM adhesion study on different layers of thin polymer films supported by silica [60], as well as the study by Li et al on the adhesion of Langmuir-Blodgett phospholipid layers atop mica [61]. The adhesion of erucamide multilayers appeared to depend on the local curvature, with a higher value obtained on the bilayer edge than on its top, resulting in pronounced adhesive response peak (marked as an asterisk) in the adhesive response profile (Figure 8D), possibly as a consequence of a higher adhesive response between the silicon AFM tip and the exposed erucamide hydrophilic headgroups at the edges of the multilamellar structure (Figure 8F).…”
Section: Multilayer Structure At Higher Erucamide Concentrationssupporting
confidence: 93%
“…The adhesive response for erucamide monolayer was likely affected by the underlying silica surface, thus slightly higher than that obtained for the bilayers or multilayers, for which the adhesive properties became dominated by the erucamide layers. This is consistent with report by Balzer et al in their AFM adhesion study on different layers of thin polymer films supported by silica [60], as well as the study by Li et al on the adhesion of Langmuir-Blodgett phospholipid layers atop mica [61]. The adhesion of erucamide multilayers appeared to depend on the local curvature, with a higher value obtained on the bilayer edge than on its top, resulting in pronounced adhesive response peak (marked as an asterisk) in the adhesive response profile (Figure 8D), possibly as a consequence of a higher adhesive response between the silicon AFM tip and the exposed erucamide hydrophilic headgroups at the edges of the multilamellar structure (Figure 8F).…”
Section: Multilayer Structure At Higher Erucamide Concentrationssupporting
confidence: 93%
“…AFM-based SMFS stands out among various single-molecule techniques [74][75][76][77] because of its high detection rate, easy operation, and wide application in measuring weak inter-or intramolecule interactions [78][79][80]. Through SMFS technique, multiple properties, such as elasticity and viscosity [81], can be analyzed in detail. At the same time, SMFS is analytic technique applied not only to measure mechanical properties of various proteins but also to manipulate single-molecule at pico-Newton scale [78], for example, probing the helical structure, unfolding -fold structure [64], and measuring intermolecular interactions.…”
Section: Principle Of Afm-based Smfsmentioning
confidence: 99%
“…Thus, SPBs are prone to be affected by their underlying substrates; it has been shown that physical properties of SPBs such as gel-to-fluid transition temperature and lateral diffusion of phospholipid molecules are influenced by their supporting substrates. The significant effects of substrate on the mechanical properties of SPBs have also been reported. For example, the extent of deformation in an SPB (which could affect its integrity) upon interaction with an external object (such as NPs or macromolecules) is determined by its stiffness, which can be influenced by the degree of interaction of the bilayer with its underlying substrate. Although there are few reports on the effect of substrate properties such as chemical composition, hydrophobicity, and roughness on spontaneous formation of SPBs, the effect of substrate interactions of SPBs and their influence on membrane stability have been mostly neglected in studies where SPBs were used as model cell membranes .…”
Section: Introductionmentioning
confidence: 99%